2020
DOI: 10.21203/rs.3.rs-109354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Prediction for Growth Using Low-Density SNP Panel in Dromedary Camels

Abstract: For thousands of years, camels have produced meat, milk, and fiber in harsh desert conditions. For a sustainable development to provide protein resources from desert areas, it is necessary to pay attention to genetic improvement in camel breeding. By using genotyping-by-sequencing (GBS) method we produced over 14,500 genome wide markers to conduct a genome- wide association study (GWAS) for investigating the birth weight, daily gain, and body weight of 96 dromedaries in the Iranian central desert. A total of 9… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The current work builds on the study by Bitaraf Sani et al [12] who reported the results of a GWAS on 96 dromedaries of several breeds in Iran. When the results of the Bitaraf Sani et al paper and the current study are compared, it was noted that a number of SNP associations within a ± 1 Mb window were in common, notably on chromosomes 7, 11, 18, 25, 31 and 33 (see S2 Table 2).…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 2 more Smart Citations
“…The current work builds on the study by Bitaraf Sani et al [12] who reported the results of a GWAS on 96 dromedaries of several breeds in Iran. When the results of the Bitaraf Sani et al paper and the current study are compared, it was noted that a number of SNP associations within a ± 1 Mb window were in common, notably on chromosomes 7, 11, 18, 25, 31 and 33 (see S2 Table 2).…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Guo et al [11] published a GWAS on haematological traits in the Bactrian camel in China. Recently, Bitaraf Sani et al [12] presented a GWAS for an Iranian dromedary population for birth weight and average growth. However, there is no study, that the authors are aware of, in the dromedary camel, that undertake a GWAS across a range of weight-for-age traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation